The basic aspect of partnership accounting - Yaacob, Zuraini; Jurina Ismail, Jurina; Jusoff, Kamaruzaman; Said, Roshima; Awang, Norasmila (Institute of Interdisciplinary Business Research, 2009)
This article describes the basic aspect of partnership accounting. The first part of this paper aims to explain the characteristics of a partnership, types of partners and partnership, partnership agreement, and advantages and disadvantages of operating as a partnership. The second part of this paper discusses an accounting procedures for a partnership firms. It highlights the method of accounting for partnership capital and the final accounts to be prepared by a partnership firm. In any partnership firms, there may be changes in partnership. A partnership firm is possible to admit new partners into the firm and it is also possible for any partner to leave the firm due to death or retirement. The third part of this paper explains factors contributing to changes in a partnership and the steps to be taken by a partnership business to record for changes in a partnership. At the end of this paper, the writers discuss the accounting procedures for dissolution of partnership. It is hoped that this paper will serve as a beneficial input to partnership businesses.